An oncolytic virus expressing a full-length antibody enhances antitumor innate immune response to glioblastoma - Bo Xu (Nature Portfolio, 2021)
Oncolytic herpes simplex virus-1 lyses cancer cells while increases their immunogenicity. Blocking the CD47 “don’t eat me” signal on cancer cells promotes their phagocytosis by macrophages. Authors here show that oncolytic viruses expressing anti-CD47 antibodies improve glioblastoma survival in mouse models.